2021
DOI: 10.1128/msphere.00039-21
|View full text |Cite
|
Sign up to set email alerts
|

Truffle Microbiome Is Driven by Fruit Body Compartmentalization Rather than Soils Conditioned by Different Host Trees

Abstract: Currently. the factors that drive the microbiome associated with truffles, the most highly prized fungi in the world, are largely unknown. We demonstrate for the first time here that truffle microbiome composition is strongly driven by associated compartments rather than by symbiotic host trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
6
11
0
Order By: Relevance
“…Additionally, a tissue specificity in bacterial community composition has also been evaluated, keeping separately the external region of ascomata, i.e., the peridium, and the internal one, i.e., the gleba that contains both vegetative hyphae and asci containing the spores (Balestrini et al, 2000 ). A decrease in alpha diversity between surrounding soil (productive soil) and the peridium, as previously reported for T. indicum (Liu et al, 2021 ), suggests that bacterial community selection occurs inside the ascomata. Outcomes of beta-diversity analysis suggest that the ascomata are composed of complex microniches, including bacteria associated with specific putative functions, i.e., nitrogen metabolism, and acclimation to sub-optimal temperatures, i.e., psychrophilic bacteria.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Additionally, a tissue specificity in bacterial community composition has also been evaluated, keeping separately the external region of ascomata, i.e., the peridium, and the internal one, i.e., the gleba that contains both vegetative hyphae and asci containing the spores (Balestrini et al, 2000 ). A decrease in alpha diversity between surrounding soil (productive soil) and the peridium, as previously reported for T. indicum (Liu et al, 2021 ), suggests that bacterial community selection occurs inside the ascomata. Outcomes of beta-diversity analysis suggest that the ascomata are composed of complex microniches, including bacteria associated with specific putative functions, i.e., nitrogen metabolism, and acclimation to sub-optimal temperatures, i.e., psychrophilic bacteria.…”
Section: Discussionsupporting
confidence: 74%
“…Fluorescence in situ hybridization (FISH) analysis (Antony-Babu et al, 2014 ) demonstrated that the bacterial colonization specifically occurred in the gleba hyphae but not in the asci. More recently, the assessment of microbial communities in T. indicum showed compartmentalization of bacterial and fungal communities in different ascoma tissues, as well as a correlation with soil samples surrounding fruiting bodies and bulk soils (Liu et al, 2021 ). A natural selective pressure on microbes has been proposed to explain the reduction of diversity and the presence of specific taxa inside the fruiting bodies (Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations